220k views
0 votes
Apply the distributive property to simplify the expression.

−3(6x + 2)

User IngoAlbers
by
5.6k points

2 Answers

1 vote

Answer:

-3(6x + 2) = -18x - 6

User Nigong
by
5.3k points
5 votes


\text{Hey there!}


\text{Distributive property}\rightarrow\text{a(b + c) = a}*\text{b + a}* \text{c = ab + ac}


\text{Now that we know what the distributive property SHOULD look like,}
\text{we can solve for your answer}


\text{-3(6x + 2)}\\\text{-3(6x) = -18x}\\\text{-3(2) = -6}


\text{ + \& - = -. so the plus sign (+) becomes a negative sign/ subtraction symbol (-)}


\boxed{\boxed{\bf{Answer:\ -18 \ - \ 6}}}\checkmark


\text{Good luck on your assignment and enjoy your day!}

~
\frak{LoveYourselfFirst:)}

User Mevlut
by
4.9k points